New finding of rare fish species for Peter the Great Bay in the Japan Sea — dragonet Draculo mirabilis (Callionymidae) - E. V. Kolpakov; P. A. Saveliev (Известия ТИНРО, 2022)
New data on finding of dragonet Draculo mirabilis in Peter the Great Bay (Japan Sea) are presented. This subtropical-lowboreal fish species is rare for this area. One adult specimen (39 mm TL) was found in the Sukhodol River estuary on sandy bottom at the depth of 0.6–0.7 m in September 2021, under the water temperature 20 оC and salinity 27 ‰. An illustrated description of this specimen is presented.